Implementasi Program Keluarga Harapan (Pkh) Dalam Menanggulangi Kemiskinan Di Kecamatan Dukuhseti Kabupaten Pati - Ihsan Zakariya Rizqi, Khoirul (Institut Agama Islam Negeri (IAIN) Kudus, 2021)
The Implementation of Program Keluarga Harapan (PKH) in Eradicate Poverty In Kecamatan Dukuhseti Kabupaten Pati. This research was conducted on the basis of the presence of poverty in Indonesia, especially in Pati province of Central Java. In on effort to overcome poverty, the government haz a wide range of intergrated poverty reduction programs. One of the programs is PKH in eradicate poverty. The research method uses descriptive qualitative research approach. The results showed implementation PKH implementation PKH in subdistrict Dukuhseti not succeeded. Not all of the contents of the policy in the PKH implemented well. The purpose of PKH is also yet to get maximum results. The persistence of the poverty, poor nutrition, mother died giving birth, and low public support to increased welfare. Suggestions that can be implemented namely evaluate the policies and giving awards to individuals.